NOTARISASI PROGRAM IN THE DISTRICT COTTAGE BOARDING BOGOR - Roestamy, Martin (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
This devotion is motivated by the fact that some regional boarding school in Bogor district has not had a notary deed of establishment boarding school. Given the importance of the notarial deed for the boarding school community service program is designed in the form of notarisasi boarding school. Advantages of the boarding school has a notary deed that is one of the beneficiaries as requirements boarding school dormitory this matter by the Ministry of Religious Affairs Directorate General of Islamic Education. Interest notarisasi boarding service activities are: 1) notarisasi establishment of boarding schools, 2) legal aid, 3) for the validation of pesantren and 4) assist in the process of getting assistance from the government Dansos West Java Province. Results from community service program that has the deed boarding school boarding school, receive legal aid, assisted in the process of getting assistance from the government Dansos West Java Province. Boarding schools that receive community service that is notarisasi boarding school located in the district of Bogor include Ibnul Hidayah Boarding School, Pondok Pesantren Al-Muklisin, Pondok Pesantren Al- Fudhaliyah, Pondok Pesantren Ibtida’ul Hudda, as well as Miftahul Huda Islamic boarding school.